Measuring fetal heart rate and variability: Fetal cardiotocography versus electrocardiography. Issue 1 (8th January 2022) - DiPietro, Janet A.; Watson, Heather; Raghunathan, Radhika S.
Abstract: Fetal heart rate variability is a key indicator of fetal neurodevelopment and well‐being. Most studies have relied on Doppler‐based fetal cardiotocography (fCTG) but recent technologies have made fetal electrocardiography (fECG) more widely available. We compared simultaneous recordings of fCTG and fECG in 131 fetuses twice during gestation (28 and 36 weeks) using a commercially available device (Monica AN24). Within‐individual correlations for fetal heart rate values, based on averaged data during 50‐min recordings, neared 1.0. Continuous and episodic measures of variability were also correlated, particularly at 36 weeks. Data collected during maternal polysomnography at 36 weeks were used to evaluate reliability of variability measures collected during the 50‐min recording. Both fCTG‐ and fECG‐derived measures of variability exhibited correspondence with variability during maternal presleep wakefulness and most sleep states. Results did not appreciably differ by data source or method used to calculate variability. fECG monitoring presented challenges, particularly at 28 weeks, when recordings with signal loss of ≤30% were available from only 27% of participants. Success rates improved to 84% at 36 weeks. fCTG was successful in over 90% of participants at each gestational age. Considerations in the selection of fECG versus fCTG in developmental research are discussed.